Oracle Web Services Manager a platform to manage, secure and extend enterprise Web services. - Barbash, Brian
As departments and organizations in the enterprise adopt Web service, the importance of managing and securing, and in some cases, extending these services to partners, grows. Using a centralized platform to do it reduces the effort and cost involved, while upping security. Web Services Manager from Oracle is designed to meet the challenge of stitching together services in large enterprises into a single management system.